Synthesis of high-entropy alloy thin films via grain boundary diffusion–assisted solid-state alloying. (15th January 2022) - Nam, Seungjin; Kim, Sang Jun; Kim, Moon J.; Quevedo-Lopez, Manuel; Hwang, Jun Yeon; Park, Eun Soo; Choi, Hyunjoo
Abstract: Herein, CoCrFeNi high-entropy alloy thin films were successfully synthesized via solid-state alloying from Al6 (CoCrFeNi)94 multilayer films, forming a CoCrFeNi-based solid solution phase with a face-centered cubic structure by optimizing Al content to prevent any oxide reaction. The microstructural and phase evolutions in the multilayer films were systematically investigated to understand the alloying behavior. Interestingly, it can be evaluated that the alloying elements could be diffused into layers, even those with nonconnected interfaces, through the grain boundaries owing to the presence of nanostructured columnar grains. Thus, these grain boundaries act as a network of diffusion paths for alloying elemental atoms to be homogenized throughout multilayer films and form the reactive phase regardless of the thermodynamic and kinetic prediction. Consequently, grain boundary diffusion–assisted solid-state alloying can be used to synthesize high-entropy alloy thin films for various multicomponent alloy systems by only controlling the layer thickness in multilayer films. Graphical abstract: Image, graphical abstract